Read With Robin: Fairy Merry Goes to School - Sara Miles
Read with Robin is a series of myths, folk tales and fairy tales, retold to encourage beginning readers to learn to read with meaning and understanding. Each story is chosen with the child in mind and makes learning to read enjoyable. The pictures illustrate the stories to give children plenty of help with word recognition. The series contains the following 1. How Bear Lost Her Tail 2. How Camel Lost His Antlers 3. How Crow Brought Daylight 4. How Snake Lost His Legs 5. How Vulture Chose His Clothes 6. Jason and the Golden Fleece 7. George and the Dragon 8. Rustam and the Dragon 9. The Dragon and the Peasant 10. The Four Dragons 11. Fairy Merry Goes to School 12. How the Old Woman Lost Her Dumpling 13. The Fairies' New Wings 14. The Fairy Harp 15. The Three Wishes 16. Beowulf and the Monster 17. Kintaro, the Golden Boy 18. Odysseus and the Cyclops 19. Perseus and Medusa 20. Theseus and the Minotaur